2023
DOI: 10.1080/20008066.2023.2263321
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from childhood sexual abuse to sexual aggression victimization and perpetration in adolescence and young adulthood: a three-wave longitudinal study

Barbara Krahé,
Isabell Schuster,
Paulina Tomaszewska

Abstract: Background: Childhood sexual abuse (CSA) has been identified as a risk factor for later sexual aggression perpetration and vulnerability factor for sexual victimization. However, the use of cross-sectional designs, the focus on female victimization and male perpetration, and the lack of evidence from outside North America limit the existing knowledge base. Objective: The study was designed to examine pathways from CSA to sexual revictimization and sexual aggression perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The necessity of prevention is especially apparent given evidence for the intergenerational transmission of trauma, such that children of parents who were abused earlier in life are more likely to be sexually abused themselves (Widom et al, 2015). More broadly, CSA predicts greater likelihood of perpetrating sexual aggression in adolescence and young adulthood (Krahé et al, 2023). Some prevention programs work directly with children, often in school settings, aiming to increase children's knowledge of and skills for preventing CSA, although it is unclear if these methods successfully lead to prevention of abuse (Fryda & Hulme, 2015; Topping & Barron, 2009; Walsh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of prevention is especially apparent given evidence for the intergenerational transmission of trauma, such that children of parents who were abused earlier in life are more likely to be sexually abused themselves (Widom et al, 2015). More broadly, CSA predicts greater likelihood of perpetrating sexual aggression in adolescence and young adulthood (Krahé et al, 2023). Some prevention programs work directly with children, often in school settings, aiming to increase children's knowledge of and skills for preventing CSA, although it is unclear if these methods successfully lead to prevention of abuse (Fryda & Hulme, 2015; Topping & Barron, 2009; Walsh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in the network global strength were found, meaning that the associations between depression, anxiety, psychosis, and PTSD symptoms were similar between male and female participants. In addition, in their longitudinal study based on a large sample of university students with three data waves covering 23 months, Krahé et al ( 2023 ) showed that the associations with later sexual victimization and perpetration held for both female and male victims of CSA.…”
Section: In This Special Issuementioning
confidence: 99%
“…Some studies report higher prevalence rates of IPV victimization in women than men, particularly more sexual abuse ( 20 - 22 ), while others report comparable estimates, particularly for physical abuse ( 23 , 24 ). What is noteworthy is that individuals exposed to maltreatment face heightened risk of IPV victimization and that this is true for different sexual orientations and sexes ( 12 , 25 - 27 ). Akin to maltreatment, IPV victimization increases psychiatric risk ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%